Good government means different things in different countries: z wprowadzeniem Boba Jessopa - Andrews, Matt (Journal of Public Governance, 2013)
Work on good governance implies a one-best-way model of effective government. This has isomorphic influences on development, whereby governments are influenced to adopt a one-size-fits-all approach to get things done. This article challenges whether such an approach exists, proposing that models actually do not hold even for the so-called effective governments. Governments look different, even if they are similarly called models of good government. This proposition is examined through a study of public financial management practices in a set of Organisation for Economic Co-operation and Development (OECD) and non-OECD countries. The study shows that effective governments are not more likely to exhibit better practice characteristics implied in one-best-way models. Good public financial management means different things in different countries. The article concludes by suggesting that good governance models give way to menus and the development community invest more time in examining why different countries select different menu items.